Inclusão escolar de crianças com necessidades educacionais especiais : práticas e perspectivas de terapeutas ocupacionais - Cardoso, Paula Tatiana (Universidade Federal de São Carlos, 2009)
More importance is being attributed to the inclusion of children with special needs in the general school education system in Brazil. In this context, there has been increased discussion regarding the use of several different knowledge fields in the elaboration and execution of child-inclusive working practices. This study s objective is to identify and characterize, in the occupational therapists point of view, the working practices used by Occupational Therapy professionals in the process of including special needs children in general school, in the State of São Paulo. The study also tried to identify strategies and actions that could be used and reinforced in this context. A survey was designed and applied, collecting data from 127 occupational therapists that work or have worked with child inclusion and who are members of the Regional Counsel of Phisioterapy and Occupational Therapy of the State of São Paulo, Crefito-3. The survey was designed by the researcher using previous studies as a reference, was submitted to the analysis of external senior professionals and professors, and was pilot-tested with a sample of occupational therapists. Three strategies were adopted in the data-collection process: sending the survey through mail, electronic mail or collecting the responses via an internet site. The data collected was subjected to descriptive-exploratory analysis and correlation analysis. The main results obtained indicate that occupational therapists that become involved in the child-inclusion process: a) get involved with child-inclusion through the medical environment, in clinics; b) work in the general education system; c) involve the family of the children and other healthcare professionals in the process; d) identify the lack of knowledge of teachers and of the school in general as the greatest single obstacle in their work, and e) recognize as high the impact occupational therapists can have in the child-inclusion process in general schools.
Keywords: Estudantes com necessidades educacionais especiais; Inclusão escolar; Terapia ocupacional; School inclusion; Children with special educational needs; Occupational therapy; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL